How do patients with eating disorders perceive and evaluate food portion sizes? A systematic review. (21st June 2020) - Dörsam, Annica Franziska; Mack, Isabelle; Kögel, Laura; Zipfel, Stephan; Giel, Katrin Elisabeth
Abstract: Objective: The selection of adequate portion sizes plays a key role in the nutritional treatment of eating disorders (EDs). There is limited knowledge concerning the estimation of portion sizes in individuals with EDs. Method: We performed a systematic review according to the PRISMA statement to synthesise current evidence in this field. Of N = 584 hits, four full‐texts were included in the qualitative synthesis. Results: While patients with anorexia nervosa (AN) tend to overestimate the size of energy‐dense food items and small to medium sized meal portions, they do not show a different estimation compared to healthy controls when judging the amount of food pieces. Large portion sizes were associated with increased anxiety in patients with AN. Discussion: The overestimation of food portion sizes seems to be driven by attitudinal and/or higher cognitive factors associated with AN. Differences between the studies are discussed and suggestions for future studies are given.